TINJAUAN HUKUM PERDATA INTERNASIONAL ATAS PERKAWINAN PENGUNGSI ROHINGYA DI INDONESIA - Rajagukguk, Chelsea Raphael; Allagan, Tiurma Mangihut Pitta (Faculty of Law, Parahyangan Catholic University, 2025)
This research explores the Private International Law (PIL) dimensions of marriages involving Rohingya refugees in Indonesia. As a transit country that has not ratified the 1951 Refugee Convention or its 1967 Protocol, Indonesia faces legal and administrative challenges in registering marriages of Rohingya refugees, either with Indonesian nationals or among themselves. Despite having the right to marry and establish families, as recognized by Article 16 of the Universal Declaration of Human Rights and Indonesia’s 1945 Constitution, they encounter significant barriers. Using a doctrinal approach, the study analyzes these issues through the lens of PIL principles and Indonesia’s existing legal framework, including the Marriage Law, Population Administration Law, Citizenship Law, Presidential Regulation Number 9 of 1975, and the 2023 Draft Bill on Indonesian PIL. The stateless status of Rohingya refugees complicates the registration of their marriages, often resulting in invalid or unregistered unions. The research focuses on determining the applicable law regarding the formal and material requirements for marriage in these cases and argues that adopting the lex loci celebrationis principle could provide a viable legal solution. It concludes by recommending the issuance of official recognition certificates for unregistered refugee marriages and the provision of citizenship for Rohingya individuals who marry Indonesian citizens, in order to uphold their fundamental human rights.